2017
DOI: 10.21605/cukurovaummfd.383432
|View full text |Cite
|
Sign up to set email alerts
|

Mobilya Sektöründe Pnömatik Zımbalama ve Vidalama İşlerinin Ergonomik Risk Değerlendirmesi

Abstract: Uygun olmayan çalışma duruşları kas iskelet sistemi rahatsızlıklarına neden olduğu gibi, üretimdeki verimin de düşmesine yol açmaktadır. Dolayısıyla ergonomi disiplininin öncelikli amacı, çalışma koşullarını iyileştirerek, iş görenin çalışma ve yaşam kalitesini yükseltmek ve verimliliği arttırmaktır. Kas iskelet sistemi rahatsızlıklarının önlenmesi amacıyla iş yerlerinde ergonomik risk değerlendirme yöntemleri uygulanmakta ve yapılan düzenlemelerle iş yükü azaltılmaktadır. Bu çalışmada, sıklıkla tekrarlanan st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Indeed, the outcomes of the relevant studies in this regard are consistent with our findings that there is clear distinction between the results of QEC and ManTRA. ALICI, et al reported that the evaluated tasks are considered to be high riskier by QEC method than ManTRA [29]. Bell and Steele also found that ManTRA classified the vacuum cleaning tasks as at risk only in arms and hands and as safe in terms of back and neck, whereas QEC resulted that there were no safe task [30].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the outcomes of the relevant studies in this regard are consistent with our findings that there is clear distinction between the results of QEC and ManTRA. ALICI, et al reported that the evaluated tasks are considered to be high riskier by QEC method than ManTRA [29]. Bell and Steele also found that ManTRA classified the vacuum cleaning tasks as at risk only in arms and hands and as safe in terms of back and neck, whereas QEC resulted that there were no safe task [30].…”
Section: Discussionmentioning
confidence: 99%